Photoelastic stress analysis of splinted and unitary implant-supported prostheses - Pellizzer, Eduardo Piza [UNESP]; Santiago Júnior, Joel Ferreira [UNESP]; Ribeiro Villa, Luiz Marcelo [UNESP]; Souza Batista, Victor Eduardo de [UNESP]; Mello, Caroline Cantieri de [UNESP]; Faria Almeida, Daniel Augusto de [UNESP]; Honrio, Heitor Marques (Springer, 2014)
The aim of this study was to evaluate the effects that splinting and different lengths of implants have on the stress distribution in implant-supported prostheses by photoelastic analysis. A total of five photoelastic resin models were made with different proposed situations, and 400 load applications were performed for the analysis. Compared with the unitary prosthesis, the splinted implant-supported prosthesis acted favorably in the distribution of stresses and strains to the implant (p < 0.001). The increase in length was a significant factor in the stress distribution (p < 0.05) and, ultimately, the overall reduction in stress. It was concluded that the splinted implant-supported prosthesis behaved better biomechanically compared with the unitary prosthesis.